1988
DOI: 10.1021/jm00403a029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfur-containing analogs of stearic acid on growth and fatty acid biosynthesis in the protozoan Crithidia fasciculata

Abstract: A variety of analogues of stearic acid in which one of the methylene groups was replaced by a sulfur atom were examined as inhibitors of growth and fatty acid biosynthesis in the trypanosomatid protozoan Crithidia fasciculata. The 8-, 9-, 10-, and 11-thiastearic acids were found to suppress the synthesis of the cyclopropane-containing fatty acid dihydrosterculic acid (9,10-methyleneoctadecanoic acid) at micromolar concentrations in the growth medium, and all but the 9-thiastearate were found to inhibit the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…These fatty acids (FA) have also been found in certain eukaryotes, including protozoa [2] and plants [3, 4]. However, few studies have documented the presence of CFA in animals [57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fatty acids (FA) have also been found in certain eukaryotes, including protozoa [2] and plants [3, 4]. However, few studies have documented the presence of CFA in animals [57].…”
Section: Introductionmentioning
confidence: 99%
“…Switching obese individuals to 1 3 species, and likely play a role in the pathogenesis of bacterial infections [1]. These fatty acids (FA) have also been found in certain eukaryotes, including protozoa [2] and plants [3,4]. However, few studies have documented the presence of CFA in animals [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The same compounds had been earlier tested on cultures of the trypanosomatids Crithidia fasciculata and Leishmania sp ., although as inhibitors of dihydrosterculic acid biosynthesis. This cyclopropane FA is exclusively synthesized by eukaryotic microbes such as species of Crithidia , Herpetomonas , Leptomonas and Leishmania , but not by trypanosomes or vertebrates, suggesting dihydrosterculic acid biosynthesis as a putative target for selective chemotherapy of leishmaniasis [16], [17]. However, our results (as obtained with T. cruzi ) suggested that the deleterious effect, at least for 10-TS, was most probably due to a specific inhibition of the SCD and a consequent drop in levels of essential FAs such as oleate and linoleate, in the Leishmania 's membranes [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies (Mika et al, ; Sledzinski et al, ), we showed that human adipose tissue and serum may contain cyclopropane fatty acids (CFA), previously examined primarily in bacteria, protozoa, and plants (Grogan & Cronan, ; Rahman et al, ; Yu, Prakash, Sweet, & Shanklin, ). Recently, the presence of CFA in humans was also confirmed by other authors, who found elevated levels of these fatty acids in adipose tissue from patients with cancer‐related and primary lymphedema (Sedger et al, ).…”
Section: Introductionmentioning
confidence: 99%